Common Agency with Moral Hazard and Asymmetrically Informed Principals - Norbert Maier (Hungarian Academy of Sciences, Institute of Economics, 2006)
In this paper, we analyze the equilibrium incentive schemes offered to an agent by two principals who can only observe correlated noisy signals of the one-dimensional action taken by the agent. We look at both cases when the two principals can or cannot cooperate in setting the terms of their incentive schemes. We show that minimizing the risk imposed on the agent may result in negative incentives being attached to the signal with the higher variation. We also find that under some conditions, the equilibrium eort level is a non- monotonic function of the correlation coec cient of the two signals. When com- paring the power of the incentive schemes oered by the two principals, we show that the principal with the higher valuation of the agent's eort or the one observing a signal with smaller variance oers more powerful incentives to the agent. Finally, we give an example of overprovision of eort in the equilibrium with non-cooperating principals compared to the case of cooperating principals. This comes at the price of higher risk and welfare in former case is lower.
Keywords: C72; D62; D82; 330; Common Agency; Moral Hazard; Moral Hazard; Prinzipal-Agent-Theorie; Asymmetrische Information; Theorie